Children's right to get exclusive breastfeeding in the Islamic law perspective - Ani Mardiantari; Ita Dwilestari (State Institute of Islamic Studies (IAIN) Salatiga, 2021)
According to Islam, exclusive breastfeeding means fulfilling the children's right to a healthy life, and it is a mothers' obligation. The government issued regulations that guarantee the children's right to exclusive breastfeeding, namely Article 52 paragraph (2) of Law Number 39/1999 concerning Human Rights, Law Number 23/2002 concerning Child Protection, and Government Regulation Number 33/2012 concerning Exclusive Breastfeeding. However, the coverage of exclusive breastfeeding in Indonesia is still relatively low, influenced by various factors. This qualitative study explored the various factors in exclusive breastfeeding and analyzed them from an Islamic Law perspective. Meanwhile, the informants were mothers with 0-6 months-old babies having exclusive breastfeeding rights. Data were collected through interviews and triangulation, including Integrated healthcare center (Posyandu) cadres and families. The results found in this study were that children's rights in obtaining exclusive breastfeeding from their mothers were not fulfilled. Various reasons were expressed to support their way by not fulfilling the rights, including the mothers' busyness causing them unable to breastfeed their children exclusively. It happens because the mothers lack knowledge about children's rights to get exclusive breastfeeding in Islamic law for two years.